Analysis of Mangrove Land Transformation in Medan Belawan, Medan Labuhan and Medan Marelan Districts - Ihsan Nur Harahap; Abdiyanto; Feby Milanie (International Journal of Society and Law, 2024)
Mangrove land transformation refers to the change in mangrove land use from its original condition to a different form, which often involves the conversion of mangrove land into other land uses that are more used by humans. Some of the consequences of mangrove transformation are the loss of habitats that are important for various types of organisms, including fish, birds, and crustaceans. This can result in a decrease in biodiversity and even the extinction of certain species, mangrove areas are more susceptible to abrasion, deterioration of water quality, reduced green open space for water catchment areas, drought, lack of oxygen levels and impact on people's livelihoods Many people living around mangrove forests depend on these ecosystems for their livelihoods, such as fishermen and collectors of non-timber forest products. The conversion of mangrove land can threaten the sustainability of their livelihoods. The use of mangrove land in Medan Belawan, Medan Labuhan and Medan Marelan Districts continues to change to other land uses, this study aims to examine the dynamics of mangrove land transformation based on policies from time to time, examine the change of mangrove land use in Medan Belawan, Medan Labuhan and Medan Marelan Districts and examine the suitability of the implementation of the RTRW spatial polar plan to the use of existing mangrove land. The method used in this study is qualitative descriptive, the research is carried out through a survey of changes in mangrove land use and identified through data processing with the Geographic Information System.